The Effect Of Fire Prevention On Restricted Area Protection Efforts At DPPU Iswahjudi Magetan - Ahmad Rifki Rivaldi; Avicena Sakufa Marsanti; Riska Ratnawati (Health Science UDINUS, 2023)
One of the fire risk factors at the Iswahjudi Aviation Fuel Depot Intoplane Services is negligence in the process of receiving, stockpiling and distribution (RSD). This is in accordance with the results of field observations that show negligence. The purpose of this study is to determine the Effect of Fire Prevention on Restricted Area Protection Efforts at the Iswahjudi Magetan Aviation Fuel Depot Intoplane Services (DPPU). This study using quantitative research with a crossectional approach, with a population of all workers and outsourced workers, totaling 27 workers. The sampling technique uses the total sampling technique. In this research, the researchers use primary data in the form of fire prevention questionnaires, and restricted area protection, with analysis using the chi square test. The results showed fire prevention with a p-value of 0,008 ≤ 0,05 so that there was an influence between fire prevention and restricted area protection efforts in DPPU Iswahjudi Magetan. Fire prevention at DPPU Iswahjudi Magetan is in the good category, while area protection efforts are restricted in the excellence category. The suggestion from the researchers to realize effective and suistainable restricted area protection efforts such as in security aspects with patrol programs and team coordination.